2017
DOI: 10.1111/petr.13067
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting a representative sample in adherence research—The MALT multisite prospective cohort study experience

Abstract: Medication adherence is an important determinant of transplant outcomes. Attempts to investigate adherence are frequently undermined by selection bias: it is very hard to recruit and retain nonadherent patients in research efforts. This manuscript presents recruitment strategies and results from the MALT (Medication Adherence in children who had a Liver Transplant) multisite prospective cohort study. MALT sites recruited 400 pediatric liver transplant patients who agreed to be followed for 2 years. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the level of patients, it is assumed that selection bias has occurred due to the large proportion of adherent patients, the small variety in ethnic background, the high percentage of patients who had a high level of education, and a long disease duration. In adherence research, the difficulty of recruiting patients who represent the general population is well recognized and often challenging (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…On the level of patients, it is assumed that selection bias has occurred due to the large proportion of adherent patients, the small variety in ethnic background, the high percentage of patients who had a high level of education, and a long disease duration. In adherence research, the difficulty of recruiting patients who represent the general population is well recognized and often challenging (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Two notable exceptions were identified in which multiple transplant centers collaborated to recruit increasingly generalizable samples of recipients. Shemesh et al conducted a multisite study of 400 pediatric liver transplant recipients, or MALT, focusing on MLVI (medication level variability index, or SD scores from blood levels) and the prediction of transplant and medical outcomes. Danziger‐Isakov et al reported on adherence barriers collected from 386 patients across 15 transplant centers (CTOT‐C).…”
Section: Discussionmentioning
confidence: 99%
“…Shemesh et al23,26,80,81 conducted a multisite study of 400 pediatric liver transplant recipients, or MALT, focusing on MLVI (medication level variability index, or SD scores from blood levels) and the prediction of transplant and medical outcomes. Danziger-Isakov et al22 reported on adherence barriers collected from 386 patients across 15 transplant centers (CTOT-C).Small sample sizes and limited statistical power restricted statistical analytic options and opportunities as well as the ability to detect important predictors.…”
mentioning
confidence: 99%
“…While some enrolled patients were participating in other CTOTC studies with multiple visits and serial monitoring, enrollment in this study was extended to any recent transplant recipient at a participating center and was not contingent on participation in a more intensive study protocol. Selection bias might be present, but it is less likely than most other adherence studies with the high rate of completion of both study visits (92/123 enrollees, 75%) and the minimization of participant burden consistent with recommendations for avoiding selection bias in the transplant populations . Further, we acknowledge the distribution of transplant type in this study, which includes a substantial proportion of lung transplant recipients, is different than the general population of pediatric organ transplant recipients which is largely renal.…”
Section: Discussionmentioning
confidence: 80%